2018
DOI: 10.3390/rel9060182
|View full text |Cite
|
Sign up to set email alerts
|

Existential and Virtuous Effects of Religiosity on Mental Health and Aggressiveness among Offenders

Abstract: Although prior research tends to show that religion has a salutary effect on mental health and a preventive effect on crime, studies explaining the religious effect, particularly those on offenders, have been limited. To address the issue, we examine whether religiosity is inversely related to negative emotions and aggressiveness among prison inmates. Additionally, we assess whether the relationships are attributable to an inmate's sense of meaning and purpose in life and/or their virtues. Specifically, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 64 publications
(71 reference statements)
7
34
0
2
Order By: Relevance
“…The positive relationships between inmates’ exposure to the Faith-Based Ministry and virtues are encouraging evidence that prison can function as a truly “correctional” institution, where virtues such as humility and gratitude are fostered, as Cullen et al (2001/2014) proposed in their concept of a “virtuous prison.” This finding also indicates that religion tends to promote virtues among prison inmates (Jang et al, 2018; see also Smith, 2003), consistent with Cullen et al’s illustration of the virtuous prison using an example of a faith-based prison program in Texas. For religious inmates, a sense of meaning and purpose in life and virtues tied to their relationship with God are also relevant because inmates who believe God’s special plan for their lives and forgiveness of their “sins” are likely grateful to God and thereby motivated to change.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The positive relationships between inmates’ exposure to the Faith-Based Ministry and virtues are encouraging evidence that prison can function as a truly “correctional” institution, where virtues such as humility and gratitude are fostered, as Cullen et al (2001/2014) proposed in their concept of a “virtuous prison.” This finding also indicates that religion tends to promote virtues among prison inmates (Jang et al, 2018; see also Smith, 2003), consistent with Cullen et al’s illustration of the virtuous prison using an example of a faith-based prison program in Texas. For religious inmates, a sense of meaning and purpose in life and virtues tied to their relationship with God are also relevant because inmates who believe God’s special plan for their lives and forgiveness of their “sins” are likely grateful to God and thereby motivated to change.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, the preventive effect of personal virtue on crime is anticipated given the very nature of crime (Jang, Johnson, Hays, Hallett, & Duwe, 2018). For example, gratitude that involves empathic emotions (Emmons & McCullough, 2003) and forgiveness, which restores broken relationships (Krause, 2018), are the opposite to crime, which “results in pain or discomfort for the victim ” (Gottfredson & Hirschi, 1990, p. 89) and is driven by vengeance in many instances (Agnew, 2006).…”
Section: The Present Studymentioning
confidence: 99%
“…However, the present study found that aggressiveness was affected by SQ by 20.6% and the remaining percentages were affected by other variables not included in this study. Some relevant studies indicate socio-demographic factors, such as gender, religion, diet, parenting style and mixed-sex education have considerable influence on a person's level of aggressiveness (Jain et al, 2018;Hofer & Spengler, 2018;Silva et al, 2017;Jang et al, 2018). An impactful factor of SQ, however, is religion or religious values a person follows.…”
Section: Resultsmentioning
confidence: 99%
“…This study has important implications for research in mental health and care. Many studies have made salutary connections between mental health and religiosity (KOENIG et al 2012;MOREIRA-ALMEIDA et al 2006;JANG et al 2018;ABDEL-KHALEK & LESTER 2017), and highlighted how religiosity can impact the likelihood of accessing mental health services (TURNER et al 2018). While some have been critical of the approaches to measuring religiosity taken in these studies, our research indicates that measuring religiosity using either the generic or mature measures of religiosity should not significantly impact the research outcomes.…”
Section: Discussionmentioning
confidence: 67%